Literature Study on The Development of a Work-Life Balance for State Civil Apparatuses (ASN) Following the Pandemic in Indonesia - ., Wahyuningrat; Tri Harsanto, Bambang; Rosyadi, Slamet; Untari, Sri (KnE Social Sciences, 2023)
The aim of this research was to formulate a development model of work-life balance for Indonesian ASN after the pandemic. Work-life balance for ASN is important since it will increase work satisfaction which will, in turn, increase their performance. Thus, both the government and state civil apparatuses (ASN) will acquire big benefits. The literature study was conducted by reviewing several journals. This research found that there are domains to determine the work-life balance for ASN. First, the government domain which contains policies that may support the realization of ASN’s work-life balance. Second, ASN’s individual domain, which contains ASN’s individual characteristics. Third, the ASN’s family domain which contains family characteristics. This study provides additional knowledge of work-life balance in the public sector in the post-pandemic context. Keywords: post-pandemic, state civil apparatus, work-life balance